Max Nettlau's utopian vision : a translation of Esbozo de historia de las utopias - Nettlau, Max, 1865-1944 (Anthem anarchist studies, 2023)
"Max Nettlau's Utopian Vision gives a historically grounded presentation of the entire literature of utopianism. Nettlau shows an encyclopedic knowledge of the subject. He passionately believes that the value of utopian thinking and class struggle should not be underestimated as utopian desire exists in all of us. Utopian thinking, according to Nettlau, stimulates the imagination and awakens the desire to attain a better life for everyone. Without it, human progress is impossible."